A multi-country survey for collecting and analyzing facts related to road traffic safety: Legislation, enforcement, and education for safer drivers. (April 2022) - Toriumi, Azusa; Abu-Lebdeh, Ghassan; Alhajyaseen, Wael; Christie, Nicola; Gehlert, Tina; Mehran, Babak; Mussone, Lorenzo; Shawky, Mohamed; Tang, Keshuang; Nakamura, Hideki
Abstract: Road traffic safety is a crucial global objective. It is important for every country to review and improve road safety policies and strategies, based on an objective understanding of its own road traffic safety situation in the world. With the aim of contributing to such a review and understanding, this study conducted a multi-country survey to gather information about various facts related to legislation, enforcement, and education, which are designed to achieve safer drivers in nine countries, by using a common format. This paper introduces the results of the survey with a particular focus on legislation and enforcement regarding speed limit violations and red-light-running as well as on education within the driving licensing systems. It highlights variations, in terms of penalty settings and enforcement levels, in different countries; it also examines the training durations necessary for acquiring a driving license and license renewal procedures. In this way, it demonstrates the potential and significance of understanding the relative position of each country in terms of road traffic safety through an international comparison despite its limited information. Highlights: Road traffic safety-related facts were examined across nine surveyed countries. Maximum legal speeds for different road types differ in different countries. Fine and penalty points for speed limit violation increase in a stepwise manner with excess speeds. Two instances of red-light running result in license suspension in five countries. The types of roads where speeding cameras are installed differ in different countries. Driving license renewal is rarely utilized as an opportunity of driver's education.